PENERAPAN MODEL PICTURE AND PICTURE PADA PEMBELAJARAN FISIKA KELAS VII SMP NEGERI PASENAN - Ovilia Putri Utami Gumay; Muhammad Ali (LP4MK STKIP PGRI Lubuklinggau, 2019)
This study aims to determine the completeness of the learning outcomes of grade VII physics in Pasenan State Middle School after the picture and picture model was applied. This research method used is quasi-experimental research. The population in this study were all students in class VII.1 Pasenan State Middle School 2016/2017 Academic Year. The sample in the study consisted of one class taken randomly by drawn, namely class VII.1, which amounted to 32 students. Data collection techniques using test techniques in the form of essays amount to ten items. With an average pretest score of 43.58 and a posttest mean value of 78.93 so that there is an increase in the value of mastery learning outcomes of 35.35, this data was analyzed using the t-test. Based on the results of the analysis of the final test data with a confidence level of 95%, it can be t_count (6.54) and t_ (table) (1,697) because t_ (count>) t_table means that Ho is rejected and Ha is accepted. learning outcomes of grade VII physics at SMP Negeri Pasenan.Penelitian ini bertujuan untuk mengetahui ketuntasan hasil belajar fisika kelas VII SMP Negeri Pasenan setelah diterapkan model picture and picture.